Antipruritic Effect of Qingpeng Ointment on the Localized Nonexudative Eczema. (15th April 2019) - Li, Yan; Xu, Wei; Li, Linfeng; Zhang, Ruina
Abstract : Objective . To evaluate the effectiveness and safety of Qingpeng ointment on eczema-associated pruritus. Trial Design and Method . This single center randomized double-blinded placebo-controlled trial enrolled 60 patients with nonexudative eczema, who were randomized at 1:1 ratio to the Qingpeng ointment and placebo control groups (n=30 in each group). The investigational and control ointment were applied on lesions twice daily for two weeks. Visual analogue scale (VAS) and pruritus symptom scores were used to assess pruritus severity, frequency, and duration. Eczema lesions were evaluated by eczema area and severity index (EASI) and lesion morphology scores. Subjects were evaluated after the first treatment and at the end of the first and second week. Results . The average age and disease duration were 50.1±13.5 years and 30.9±16.0 weeks, respectively. Baseline EASI and VAS scores were similar between the two groups. VAS scores of the Qingpeng ointment group were significantly lower than those of the placebo control group at 10 minutes and 30 minutes after the first treatment and the first and second week follow-up (all P < 0.05). The scores of pruritus severity, frequency, and duration were significantly lower in the Qingpeng ointment group than in the control group at the end of week 1 and week 2 of the study (all P < 0.05). The scores of lesion morphology at the end of week 1 of the study were not significantly different between the two groups, but the Qingpeng ointment group showed significantly lower score than the placebo control group at the end of week 2 of the study. No adverse event was observed in the study. Conclusion . Qingpeng ointment can effectively alleviate pruritus and reduce skin lesions in patients with nonexudative eczema. The antipruritic effects occurred early and at a greater magnitude than the effects on lesion attenuation.